Past subjunctive or consecutive mood? - Posthumus, L. C. (South African Journal of African Languages, 1991)
Inconsistent use of the terms 'consecutive mood' and 'past tense of the subjunctive mood', with reference to verb forms such as walimala in the sentence. Uwile walimala 'He fell and got hun', has necessitated a thorough investigation into the characteristics of this verb form. Differentiating distinctions on the semantic, syntactic, and phonological levels between the remote past tense of the indicative, situative and qualificative/relative moods and the so-called 'past tense of the subjunctive mood' compel the linguist not to regard the verb forms in question as past subjunctive, or as tense forms at all.